Tuning hydrophobicity of a fluorinated terpolymer in differently assembled thin films. Issue 8 (7th February 2017) - Ok, Salim; Sheets, Julia; Welch, Susan; Kaya, Savas; Jalilov, Almaz; Cole, David R.
ABSTRACT: In the current report, casting from good solvent (acetone) and casting from mixed solvent and nonsolvent were employed for preparing thin films of terpolymer ofT etrafluoroethylene (TFE), H exafluoropropylene (HFP), andV inylidene fluoride (VDF) (THV), on silicon wafers. These films revealed various morphologies and wetting behaviors depending on the solution concentration, temperature, and thin film preparation method. The THV thin films prepared by casting from good solvent showed smooth morphology with holes. The thin film prepared from a 3 wt % THV/acetone solution by casting from good solvent at 15 °C demonstrated spheres in addition to the smooth morphology, while the thin film prepared from a 5 wt % THV/acetone solution at 15 °C by casting from good solvent had a mesh‐like structure with some linked spheres. Casting the thin films from mixed solvent and nonsolvent resulted in various morphologies such as different sphere sizes embedded in a dense film layer, and hexagonal close packed structures. The thin films prepared by casting from good solvent showed a slightly hydrophobic character, with a measured water contact angle of approximately 99°, while the nonsolvent cast films had a water contact angle as high as 145°. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 643–657 Abstract : Thin films of fluorinated terpolymer of THV prepared by casting from good solvent yielded smooth morphology, versus films prepared by casting from mixed solvent and nonsolvent yielding spheres and dense layers. In comparison to casting from good solvent, hydrophobicity of THV increased by approximately 43% on the thin films cast with mixed solvent and non‐solvent.